ENHANCING MOTIVATION AND ENGLISH LEARNING OUTCOMES THROUGH PROBLEM-BASED LEARNING: A STUDY ON ELEMENTARY TEACHER EDUCATION STUDENTS AT UNIVERSITAS MUHAMMADIYAH GORONTALO - Amara, Basri Usman (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2025)
This study aims to analyze the effect of the Problem Based Learning (PBL) model on the motivation and learning outcomes of English among students of the Elementary School Teacher Education (PGSD) program at Universitas Muhammadiyah Gorontalo. The background of this research stems from the low level of student engagement in English learning, which impacts their academic achievement. PBL was chosen as it emphasizes solving contextual problems relevant to students’ lives, thereby expected to enhance active participation, curiosity, and critical thinking skills. This research employed a quasi-experimental method with a pretest–posttest control group design. The sample consisted of 50 students divided into an experimental group (using PBL) and a control group (using conventional teaching). Research instruments included a learning motivation questionnaire based on the Motivated Strategies for Learning Questionnaire (MSLQ) and an English achievement test. Data analysis was conducted using independent t-tests and paired t-tests. The results revealed a significant improvement in learning motivation and achievement in the experimental group compared to the control group (p < 0.05). The implementation of PBL proved effective in increasing student engagement, fostering independent learning, and improving academic outcomes. These findings recommend the application of PBL as an innovative learning strategy for English courses in PGSD programs.